2002
DOI: 10.1117/12.466653
|View full text |Cite
|
Sign up to set email alerts
|

<title>Thermal imaging of brain tumors in a rat glioma model</title>

Abstract: We have explored the capability of thermal imaging for the detection of brain tumors in a rat glioma model. Fourteen Wistar rats were injected stereotactically with 100,000 C6 glioma cells. Approximately one and two weeks post implantation, the rats were undergone bilateral craniotomy and the exposed brain surface was imaged with a short wave thermal camera. Thermal images were obtained at both low (~28.7°C) and high (~38 °C) core temperatures. Temperature gradients between the tumor site and the contralateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…Although the literature about the application of thermal IRI in neurosurgery is sparse, it is known that the presence of brain neoplasms alters the thermal homeostasis of the surrounding tissue. Indeed, studies on animal and human models reported a lower temperature pro le of primary tumors of glial origin than the surrounding parenchyma [18][19][20]. Gorbach et al showed that glial tumors have a temperature 0.5-2.0°C lower than the surrounding healthy brain parenchyma [19].…”
Section: Introductionmentioning
confidence: 99%
“…Although the literature about the application of thermal IRI in neurosurgery is sparse, it is known that the presence of brain neoplasms alters the thermal homeostasis of the surrounding tissue. Indeed, studies on animal and human models reported a lower temperature pro le of primary tumors of glial origin than the surrounding parenchyma [18][19][20]. Gorbach et al showed that glial tumors have a temperature 0.5-2.0°C lower than the surrounding healthy brain parenchyma [19].…”
Section: Introductionmentioning
confidence: 99%